Heat kernel estimates for FIN processes associated with resistance forms - Croydon, D; Hambly, B; Kumagai, T (Elsevier, 2018)
Quenched and annealed heat kernel estimates are established for Fontes–Isopi–Newman (FIN) processes on spaces equipped with a resistance form. These results are new even in the case of the one-dimensional FIN diffusion, and also apply to fractals such as the Sierpinski gasket and carpet.